PENGUJIAN BIAS PERILAKU: GAMBLER’S FALLACY, HALO EFFECT, DAN FAMILIARITY EFFECT DI PASAR MODAL INDONESIA - Djojopranoto, Riana Rahmawati; Mahadwartha, Putu Anom (UI Scholars Hub, 2016)
This study aims to examine the biased behavior of investor in uptrend and/or downtrend market in Indonesian stock exchange. Behavioral bias is indicated by three variables: gambler’s fallacy, halo effect, and familiarity effect. Data were collected using questionnaire and distributed to 384 respondents. First, questionnaires were analyzed using frequency distribution. Second, questionnaires were assessed using Likert scale and analyzed using one sample t-test and paired t-test to answer the hypothesis and research questions. The result shows that gambler’s fallacy exists in investors when they trade in uptrend stock market, but does not exist in downtrend stock market. Halo effect does not exist when they trade in uptrend and downtrend stock market. Meanwhile, familiarity effect exists when they trade in uptrend and downtrend stock market. In uptrend stock market, familiarity effect was greater than that of the downtrend stock market. Based on the result, this research concluded that in general, investors in Indonesian stock market are irrational in decision making process. In the uptrend market, behavioral bias is potentially greater than that in the downtrend market as indicated by the occurrence of gambler’s fallacy and familiarity effect. Meanwhile, in the downtrend market, the behavioral bias is indicated by familiarity effect.